Transformasi Nilai-Nilai Kearifan Lokal Pada Seni Angklung Sebagai Dasar Pengembangan Civic Culture Masyarakat. - Deby Elsera (Civic Edu : Jurnal Pendidikan Kewarganegaraan, 2022)
This study aims to determine how the transformation of local wisdom values in the art of angklung as the basis for developing community civic culture. This research is motivated by the author's anxiety about regional cultural shocks in people's lives which have now undergone modernization, where global culture enters and nests without being prevented. So that the values of local wisdom in it are eroded and even disappear, this will erode the character of the Indonesian nation contained in civic culture which is reflected through culture and art. This research uses a phenomenological study method with a qualitative approach. This research shows several things, including: (1) The values of local wisdom in the art of angklung in Angklung Village are transformed in the way the community behaves, where local culture is used as a guideline, source of knowledge, and life strategy in carrying out daily activities, which is poured into a social institution. (2) The transformation of local wisdom values can be realized through continuous innovation to adapt to the changing situation and conditions of the times, which is carried out by adapting the traditional culture that is owned, namely the art of angklung with the influence of developing foreign cultures. (3) The values of local wisdom can be effectively realized through the field of art, because art is formed from culture which is the result of community creation which is passed down from generation to generation which is used as a tradition and identity of a society. The arts and culture are merged into a civic culture that supports the community because it is related to social behavior in society so that it can be used as a national identity.